2013
DOI: 10.1152/ajplung.00226.2012
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated structural decrements in the aging female rhesus macaque lung compared with males

Abstract: -Aging is associated with morphometric changes in the lung that lead to decreased lung function. The nonhuman primate lung has been shown to have similar architectural, morphological, and developmental patterns to that of humans. We hypothesized that the lungs of rhesus monkeys age in a pattern similar to human lungs. Thirty-four rhesus monkeys from the California National Primate Research Center were euthanized, necropsied, and the whole lungs sampled. Stereological analysis was performed to assess the morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Previous estimates of the number of alveoli in the lungs of rhesus macaques were done using the same methodology (14,19,20). The values are reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates of the number of alveoli in the lungs of rhesus macaques were done using the same methodology (14,19,20). The values are reported in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). Rhesus data were based on previous reports (14,19) and rat alveoli numbers (3, 24, 25). (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Three papers on the postnatal development and aging of the rat, the nonhuman primate, and the human lung will be addressed (48,49,147). All of the three papers used state-of-the-art stereology and present a portfolio of detailed methods to assess lung alveolarization or age-associated loss of alveoli.…”
Section: Biological Observations Obtained By Stereological Methodsmentioning
confidence: 99%
“…Their data clearly show that the major process of alveolarization takes place exponentially through the first 2 yr of postnatal life but continues at a much slower rate during adolescence. The loss of alveoli during aging was studied by the same group in the rhesus macaque and differentiated between male and female monkeys (48). Their data demonstrate a more pronounced loss of alveoli in the female monkeys compared with the males.…”
Section: Biological Observations Obtained By Stereological Methodsmentioning
confidence: 99%
“…However, later data using appropriate stereological techniques showed that alveoli increase in number, but not size during postnatal development in rhesus monkeys (187). As rhesus monkeys age, there is a significant loss of alveoli that is 30% greater in postmenopausal females than males (134). The great apes that assume an upright position exhibit anatomical relationships among lungs, thorax, heart, and diaphragm that closely resemble those in humans.…”
Section: Matching the Components Of Pulmonary Gas Transport And The Cmentioning
confidence: 99%